Serving God and Mammon: The 'Minerals-Railway Complex' and its Effects on Colonial Public Finances in the British Cape Colony, 1810-1910 - Abel Gwaindepi (African Economic History Network (AEHN), 2019)
The resource curse literature underscores the fact that extractive economies face challenges in diversifying their economies. What is less explored are the public finance challenges encountered in these economies when the extractive industries are completely privatized. Using a recently compiled dataset on public revenues, expenditures and debt, this paper explores the nexus between the privatized extractive sector operations and public finance policies of the Cape Colony between 1810 and 1910. The paper finds that despite the natural resource endowment, the Cape Colony became heavily indebted and had huge budget deficits by the time it joined the Union of South Africa in 1910. After the discovery of diamonds, competition for resource-rents caused a slowdown and in some instances reversed the progress made in consolidating state institutions. The drive towards a national program of development inherent in self-governing colonies was overpowered when the competition for resource-rents culminated in rent-seeking led by the interests in the monopolized extractive sector. Rather than being the main source of government revenues and a basis for inclusive economic progress, as expected in a selfgoverning settler colony, diamonds became a trap through the operations of what I call a 'Minerals-Railway complex'. The insights from the study have important implications for our understanding of both settler colonialism in Sub-Sahara Africa as well as the management of natural resources in developing economies.
Keywords: N17; N27; N37; N47; N57; N77; 330; Resource curse; rent-seeking; South Africa; railways; economic history